Outcomes of Age-Friendly Health Systems: Return to Clinic After 4Ms Care Delivery - Grace Q. Armstrong MPH; Heba M. Aldossary MSN, RN; Jessica Bingham BSN; Lilia Pino PhD, RN, FNP-C; Anne Pohnert DNP, RN, FNP-BC; Mary A. Dolansky PhD, RN, FAAN; Nicholas K. Schiltz PhD (Inquiry: The Journal of Health Care Organization, Provision, and Financing)
The Age-Friendly Health System (AFHS) movement continues to grow in the United States as more health systems implement the 4Ms framework. Despite this growth, there are relatively few studies that evaluate outcomes related to AFHS implementation. This study assessed patient satisfaction with AFHS by analyzing the rate at which patients returned to the clinic for future health care, serving as a measure of quality. A retrospective cohort design using electronic health record (EHR) data obtained from patients 65 years of age and older who received care at a large national network of convenient care clinics in the U.S. ( N  = 987,197) between January 2021 and March 2024. We assessed the level of AFHS 4Ms care received by these individuals in relation to their subsequent visit back to the clinic through descriptive statistics, a time-to-event analysis using the Kaplan-Meier cumulative incidence approach, and a Cox proportional Hazards model, adjusted for age, race, sex, prior appointments, and number of ICD-10 code diagnoses. Throughout the study period, patients who received complete AFHS 4Ms care exhibited greater rates of returning to the convenient care clinic compared to those who received partial or no 4Ms 4Ms care. Kaplan-Meier curves demonstrated that the cumulative probability of returning to the clinic was higher in patients that received 4Ms over time, compared to patients that did not receive 4Ms. Results from the Cox Proportional Hazards model demonstrated a risk ratio of 3.91 ( p  < .001) of returning to the clinic, after adjustment. The results indicate that patients are more likely to seek additional care in the future at the same health system when they receive complete 4Ms care, possibly due to increased satisfaction with care. As patient satisfaction is an indicator of quality care, this finding can further inform and spread the AFHS movement.